Use of Qris in the Tourism Support Sector in West Sumatra Tourist Destinations with the Technological Acceptance Model (TAM) Approach (Survey on West Sumatra Tourists) - Agung Perdana; Eri Besra; Sari Lenggogeni (Jurnal Bisnis dan Manajemen, 2023)
Abstract:This study aims to analyze the use of QRIS in the tourism support sector in west sumatra tourist destinations with the technological acceptance model (TAM) Approach (Survey On West Sumatra Tourists). The type of research used in this research is explanatory research, with the research method being an explanatory survey that emphasizes quantitative methods. The sample is 250 tourists who use QRIS as a means of payment in the tourism support sector in West Sumatra tourist destinations. The sampling technique was purposive sampling. The data analysis method uses Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of the study show that perceived usefulness has a significant effect on behavioral intention to use QRIS. Perceived ease of use has a significant effect on behavioral intention to use QRIS. Perceived usefulness has a significant effect on the attitude toward using QRIS. Perceived ease of use has a significant effect on the attitude toward using QRIS. Attitude toward using has a significant effect on behavioral intention to use QRIS. Perceived usefulness has no significant effect on behavioral intention to use through attitude toward using QRIS. Perceived ease of use has a significant effect on behavioral intention to use through attitude toward using QRIS.Keywords: Perceived Usefulness; Perceived Ease Of Use; Attitude Toward Using; Behavioral Intention To Use